Cutting the Gordian knot of abiotic stress in grapevine: from the test tube to climate change adaptation - Carvalho, Luísa C. (2019)
In Mediterranean climate areas, the available scenarios for climate change suggest an increase in the frequency of heat waves and severe drought in summer. Grapevine (Vitis vinifera L.) is a traditional Mediterranean species and is the most valuable fruit crop in the world. Currently, viticulture must adjust to impending climate changes that are already pushing vine-growers toward the use of irrigation, with the concomitant losses in wine quality, and researchers to study tolerance to stress in existing genotypes. The viticulture and winemaking worlds are in demand to understand the physiological potential of the available genotypes to respond to climate changes. In this review, we will focus on the cross-talk between common abiotic stresses that currently affect grapevine productivity and that are prone to affect it deeper in the future.We will discuss results obtained under three experimental stress conditions and that call for specific responses: (1) acclimatization of in vitro plantlets, (2) stress combinations in controlled conditions for research purposes, (3) extreme events in the field that, driven by climate changes, are pushing Mediterranean species to the limit. The different levels of tolerance to stress put in evidence by the plasticity of phenotypic and genotypic response mechanisms, will be addressed. This information is relevant to understand varietal adaptation to impending climate changes and to assist vine growers in choosing genotypes and viticulture practices